Impact Of The Taxpayer Understanding And Awareness, Tax Sanctions, Fiscus Services, E-Filing System On Taxpayer Compliance In Jakarta During The Covid-19 Pandemic - Karsam, Karsam; Budiandru, Budiandru (Jurnal Pajak dan Keuangan Negara (PKN), 2023)
Objective – The objective of this paper is to examine the ways understanding and aware of taxpayers are regarding understanding and awareness of taxes, penalties, tax authorities, and electronic filing systems for taxpayers regarding taxpayer compliance in the DKI Jakarta area.. Design/methodology – The method of this study is quantitative. As part of this quantitative study, it is not in the form of statistics, but through the process of collecting data by distributing questionnaires and using sampling methods that aim to eliminate the problem of extensive data collection to make population conclusions so that data collection will be practical, cost-effective and convenient. The sampling technique is measurement model analysis in the outer model and structural model analysis in the inner model employing SmartPLS 3 Multivariate Structural Equation Model (SEM). Results – Partially the findings of this research suggest that the electronic filing system affects taxpayer compliance. Understanding and awareness of taxpayers has tax sanctions have had no effect on taxpayer compliance no effect on tax authorities' and taxpayers' compliance services have no effect on taxpayer compliance. The square root of R, or R2 simultaneously is 0.504 or 50.4%, This indicates that factors that influence compliance by taxpayers understanding and awareness of taxpayers, tax sanctions, tax authorities and e-filing systems of 50.4%. The contribution of this research shows that the electronic filing system a impact on compliance by taxpayers, in this instance taxpayers must learn more about taxes and the government must provide education and an adequate system for taxpayers. Research limitations/implications – The weakness of this study is that the number of respondents who are taxpayers registered at the DKI Jakarta KPP is still limited and does not represent the sample as a whole. The implication is that conclusions cannot be generalized and cannot be used as the main reference The number of taxpayers during a pandemic situation was reluctant to report and pay taxes, this had an impact on the level of compliance Novelty/Originality – The novelty of this study is that there are samples taken from the Covid pandemic, the variables of awareness and concern use different indicators.